Depression and Cognitive Decline: Factors Related to Demographics and Psycho Pharmacotherapy on Elderly in Nursing Homes - Soares, Edvaldo [UNESP]; Rossignoli, Patrícia de Souza [UNESP] (My University, 2014)
Objectives: To identify the prevalence of neuropsychiatric disorders, especially DP and CD, on a sample of nursing home residents, relating this prevalence with some aspects of the demographics and psycho pharmacotherapy. Methods: 48 elders from two different nursing homes were selected. The collection of demographic and pharmacological data was made utilizing medical records. The medication was classified according to the Anatomical Therapeutic Chemical Code (ATC) criteria. The Geriatric Depression Scale (GDS 30) and the Mini Mental State Examination (MMSE) tests were utilized to determine the prevalence of DP and CD. Results: It was observed in the sample a high incidence of DP and CD among the researched elders. More schooling individuals tend to present less CD. Individuals with less CD indicatives present less symptomatology for DP. Of all the researched elders, 54,2% are submitted to psycho pharmacotherapy. Of all the consumed medicine, 16,5% belonged to the class of neuropsychiatric medicine. The medicated elders present, in average, a larger symptomatology for DP (12 points/average/GDS) than the non-medicated elders (9,9 points/average/GDS). The inverse occurs in relation to the CD indicatives. The use of psychotropics, especially in association, can have negative effects related to depression and cognition. Discussion: The pharmacotherapy, characterized for the polymedication and chronicity, especially of neuropsychiatric medicines, deserves special attention among elders, because the data suggest a significant relation between the utilization of medicines, singly or in association, and the increase of CD and DP. In addition, the data suggest that DP is a risk factor for CD and DM.
Keywords: Cognitive Decline; Depression; Elderly; Nursing Home; Psycho Pharmacotherapy